Characteristic of chemical and sensory of stick product which fortified with yellowfin tuna flour - Vanessa Natalie Jane Lekahena (Agrikan: Jurnal Agribisnis Perikanan, 2019)
Snack is defined as food consumed between regular meals which are liked by all people, so it becomes a habit to get rid of hunger before the main meal. Stick is a long flat snack, has a savory taste and crunchy, made from a mixture of flour, fat, eggs and water, which is processed by frying or baking. Fish sticks are processed snacks made from a mixture of flour, seasoning, margarine, eggs and water and additional fish meat or fish flour, then formed to flat shapes with a length of ± 6-7 cm and frying with oil at 170 °C till golden yellow This study aims to determined the chemical characteristics and evaluation of sensory fish sticks fortified with yellowfin tuna flour. The results of this study can be concluded that the percentage of yellowfin fish flour fortified on stick product effected to the chemical characteristics of parameters moisture contents (2.76 - 3.63%), ash (2.66 - 5.02%), fat (16.15 - 22.55%) protein (7.39 - 11.72%), and carbohydrates (57.94 - 70.17%) produced by yellowfin fish sticks. Fortification of yellowfin tuna flour has an effected on the sensory characteristics of fish sticks on the attributes of aroma and taste, while not affecting the appearance and texture attributes.